Diffractive Optical Elements with a Large Angle of Operation Recorded in Acrylamide Based Photopolymer on Flexible Substrates - Hoda Akbari; Izabela Naydenova; Lina Persechini; Sean M. Garner; Pat Cimo; Suzanne Martin (International Journal of Polymer Science)
A holographic device characterised by a large angular range of operation is under development. The aim of this study is to increase the angular working range of the diffractive lens by stacking three layers of high efficiency optical elements on top of each other so that light is collected (and focussed) from a broader range of angles. The angular range of each individual lens element is important, and work has already been done in an acrylamide-based photosensitive polymer to broaden the angular range of individual elements using holographic recording at a low spatial frequency. This paper reports new results on the angular selectivity of stacked diffractive lenses. A working range of 12° is achieved. The diffractive focussing elements were recorded holographically with a central spatial frequency of 300 l/mm using exposure energy of 60 mJ/cm2 at a range of recording angles. At this spatial frequency with layers of thickness 50 ± 5 µm, a diffraction efficiency of 80% and 50% was achieved in the single lens element and combined device, respectively. The optical recording process and the properties of the multilayer structure are described and discussed. Holographic recording of a single lens element is also successfully demonstrated on a flexible glass substrate (Corning(R) Willow(R) Glass) for the first time.